Introducing Pharm. D. Programme in India: A Need of the Day - JS, Patil; RV, Kulkarni; SC, Marapur; VV, Dalavi (Indian Journal of Pharmacy Practice)
This article aims to focus on need of changes in the Pharmacy education in India and proposed role of clinical Pharmacist in the healthcare system. A thorough search of literature was carried out and critically compared the recently introduced Pharm. D. programme with the same of other countries especially United States of America. An attempt was also made to identify the need of Pharm. D. programme, which is going to produce clinical Pharmacists as per the requirement of our healthcare sector. This study made an attempt to narrate the role of Pharmacist in clinical and biomedical research and also tried to focus on the scope of pharm. D. graduates across the world. This is not the right time to say some thing on Pharm. D. programme, because it is in the stage of infancy. The Pharmacy Council of India is appreciable for introducing this programme. Hence, the study critically reviewed and tried to draw attention of our regulatory bodies to take attention for successfulness of this programme.The study also identified some regulatory and upgradational suggestions to our government authorities and policy makers, which may help in successful implementation of Pharm. D. programme in India.
Keywords: Pharm. D. programme; Clinical pharmacy; Healthcare sector